A new species of a rare genus, Truxonchus quangi sp. n. (Mononchida, Anatonchidae) from bat xat nature reserve in Lao Cai Province, Vietnam - Vu, Tam T.t. (Zootaxa, 2021)
Truxonchus quangi sp. n. is described and illustrated from Vietnam. Females of the new species are characterized by large body size (L = 4.8-5.8 mm); barrel shaped buccal cavity of large size (105-113 x 66-73 µm) with one dorsal tooth and two subventral teeth posteriorly directed, of equal shape, size and apex position; dorsal tooth apex located 36-39% of buccal cavity length from its base; reproductive system didelphic-amphidelphic, vagina long, 39-45% of corresponding body width, with distinct par refringens vaginae, sclerotized pieces rounded in optical section; tail long, filiform, ventrally arcuate, with three small caudal glands in tandem and prominent subventral spinneret. The new species is close to T. dolichurus but differs by the larger buccal cavity, more anterior position of the dorsal tooth apex, more anterior vulval position and presence of advulval pores.